Thermal and radiation shielding characteristics of erbium ions doped zinc tellurite glasses - Nazrin, S.n; Halimah, M.K.; Tahir, M.H.M.; Amami, Mongi; Hamid, Mohamad Amin; Gowda, G.V. Jagadeesha; Hisam, R; Sha'ari, M. Imran; Syafiq, M.Y. Muhammad; Alrowaili, Z.A.; Al-Buriahi, M.S. (Elsevier, 2024)
Tellurium, zinc, and erbium oxides glasses are made using the melt-quenching technique. The XRD results show that the glass samples are naturally amorphous. The TeO4 units' extended vibration are performed using FTIR. On the other hand, the TeO3 as well as Er2O3 are detected using deconvolution. When the concentration of erbium ions increases, the density and molar volume will also increase. The high value of thermal diffusivity at 0.02 and 0.03 M fractions, a large value of glass stability (greater than 100 °C), and strong thermal stability are excellent for fibre drawing. As a result, the highest linear attenuation coefficient (LAC) values are found for the sample with 5 mol% Er2O3 content, where the values drop suddenly from 0.95744 to 0.21065 cm−1 over the tested energy which ranges between 0.284 and 2.51 MeV. Among the TZEr samples, TZEr5 has the lowest half-value layer (HVL) values ranging from 0.00243 to 0.08252 cm. Thus, both LAC and HVL are considered as suitable options for radiation shielding materials.